Automotive Cybersecurity An Introduction to ISO/SAE 21434. - Ward, David (SAE International, 2021)
Industries, regulators, and consumers alike see cybersecurity as an ongoing challenge in our digital world. Protecting and defending computer assets against malicious attacks is a part of our everyday lives. From personal computing devices to online financial transactions to sensitive healthcare data, cyber crimes can affect anyone. As technology becomes more deeply embedded into cars in general, securing the global automotive infrastructure from cybercriminals who want to steal data and take control of automated systems for malicious purposes becomes a top priority for the industry. Systems and components that govern safety must be protected from harmful attacks, unauthorized access, damage, or anything else that might interfere with safety functions. Automotive Cybersecurity: An Introduction to ISO/SAE 21434 provides readers with an overview of the standard developed to help manufacturers keep up with changing technology and cyber-attack methods. ISO/SAE 21434 presents a comprehensive cybersecurity tool that addresses all the needs and challenges at a global level. Industry experts, David Ward and Paul Wooderson, break down the complex topic to just what you need to know to get started including a chapter dedicated to frequently asked questions. Topics include defining cybersecurity, understanding cybersecurity as it applies to automotive cyber-physical systems, establishing a cybersecurity process for your company, and explaining assurances and certification.